Asuransi dalam Perspektif Hukum Islam - Abduh Muhammad (Al-'Adl, 2009)
Insurance as one of the transaction form in muamalah between the human being economical can give a positive impact on prosperity. In one side, the insured [party/side], given a premium to underwriter party/side (insurance), he obtains; gets property guarantee according to Akad of insurance party/side also with premium which he was obtaining of from the insured party/side can develop the effort him. By juridic, especially in Islam law, the problem of insurance is new matter because do not be found in a study of fiqh classic. Along with that, the problem of insurance is the problem of ijtihad which has, of course, generated controversy among all Moslem scholars, there is enabling, but there is also extreme do isn’t it.